Do FDI firms employ more workers than domestic firms for each dollar of assets? - Ando, Sakai,Wang, Mengxue (International Monetary Fund, 2020)
This paper studies whether FDI firms employ more workers than domestic firms for each dollar of assets. Using the Orbis database and its ownership structure information, we show that, in most economies, domestic firms tend to employ more workers per asset than FDI firms. The result remains robust across individual industries in the case study of the United Kingdom. The analysis of the switchers (ownership changes from domestic to foreign or vice versa) suggests that ownership changes do not have an immediate impact on the employment per asset. This result suggests that different patterns of employment per asset seem to come from technological differences rather than from different ownership structures
10.5089/9781513536323.001
Keywords: Graue Literatur; Financial Risk Management; Public Finance; International Investment; Long-term Capital Movements; Unemployment; Wages; Intergenerational Income Distribution; Aggregate Human Capital; Aggregate Labor Productivity; National Government Expenditures and Related Policies: General; International Financial Markets; Finance; Labour; income economics; Public finance & taxation; Foreign direct investment; Employment; Public expenditure review; Special purpose vehicle; Balance of payments; Labor; Expenditure; Asset and liability management; Investments; Foreign; Employment; Economic theory; Expenditures; Public; Asset-liability management; Exports and Imports; FDI; Job Creation; Orbis; Ownership